2021
DOI: 10.1002/anie.202101322
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength‐Selective Photopolymerization of Hybrid Acrylate‐Oxetane Liquid Crystals

Abstract: We report on the wavelength‐selective photopolymerization of a hybrid acrylate‐oxetane cholesteric liquid crystal monomer mixture. By controlling the sequence and rate of the orthogonal free‐radical and cationic photopolymerization reactions, it is possible to control the degree of phase separation in the resulting liquid crystal interpenetrating networks. We show that this can be used to tune the reflective color of the structurally colored coatings produced. Conversely, the structural color can be used to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Finally, Hoekstra et al utilized a wavelength selective approach to photopolymerize liquid crystalline (LC) achiral acrylates and chiral oxetane monomers via combined, orthogonal free‐radical and cationic ROP reactions (Figure 25A). 235 These two polymerizations were conducted either simultaneously or sequentially leading to differing LC ordering within the films. It was demonstrated that the simultaneous polymerization of both the acrylate and oxetane monomers (320–500 nm) led to the formation of an interpenetrating LC networks (LCNs) possessing red structural color and the cholesteric mesophase throughout the entire coating, according to AFM (Figure 25B).…”
Section: Polymerization Methodologies Mediated Using Orthogonal External Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Hoekstra et al utilized a wavelength selective approach to photopolymerize liquid crystalline (LC) achiral acrylates and chiral oxetane monomers via combined, orthogonal free‐radical and cationic ROP reactions (Figure 25A). 235 These two polymerizations were conducted either simultaneously or sequentially leading to differing LC ordering within the films. It was demonstrated that the simultaneous polymerization of both the acrylate and oxetane monomers (320–500 nm) led to the formation of an interpenetrating LC networks (LCNs) possessing red structural color and the cholesteric mesophase throughout the entire coating, according to AFM (Figure 25B).…”
Section: Polymerization Methodologies Mediated Using Orthogonal External Stimulimentioning
confidence: 99%
“…Different reaction times led to different visible light reflectances with the full visible region being obtained selectively (D) leading to the fabrication of complex, colored films using photomasks (E and F). Reproduced with permission from Hoekstra et al 235 Copyright 2021, Wiley…”
Section: Polymerization Methodologies Mediated Using Orthogonal External Stimulimentioning
confidence: 99%
“…Polymerization-induced phase separation (PIPS), the spontaneous segregation of otherwise miscible components upon an increase in the molecular weight of at least one of the components, has offered a distinct pathway for generating thermoset polymers with well-defined nanostructures and microstructures. Indeed, various morphologies have been produced with the PIPS strategy including co-continuous, isolated or fused globular structures, lamellae, and cylinders , with applications for membranes, sorbents, , functional coatings, , and UV-cured dental materials. , Owing to their versatile and pre-designed molecular nature, block copolymers are well suited for PIPS in thermosets where the molecular weight and volume fraction of polymer blocks regulate the domain size and morphology of the phase-separated systems. Early examples of block copolymer-driven PIPS employed amphiphilic copolymers blended with epoxy systems to yield highly ordered domains down to tens of nm. , However, the lack of a covalent bond connecting the secondary polymer and the thermoset matrix in these early works resulted in the expulsion of the copolymers from the matrix and set a lower bound for the domain size (e.g., above ∼10 nm) .…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization-induced phase separation (PIPS), the spontaneous segregation of otherwise miscible components upon an increase in the molecular weight of at least one of the components, has offered a distinct pathway for generating thermoset polymers with well-defined nanostructures and microstructures. Indeed, various morphologies have been produced with the PIPS strategy including co-continuous, 1−3 isolated or fused globular structures, 4−6 lamellae, 7−9 and cylinders 10,11 with applications for membranes, 12−14 sorbents, 15,16 functional coatings, 17,18 and UV-cured dental materials. 19,20 Owing to their versatile and pre-designed molecular nature, block copolymers are well suited for PIPS in thermosets where the molecular weight and volume fraction of polymer blocks regulate the domain size and morphology of the phase-separated systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we reported on the wavelength-selective photopolymerization of a hybrid acrylate-oxetane cholesteric liquid crystal monomer mixture in which there was no difference in cross-link density between the acrylate and oxetane LC networks. 34 In this work, the fabrication of an LC-IPN based on acrylate and oxetane LC monomers for use as shape memory materials and soft actuators is reported. The LC-IPN can be prepared in a one-pot fashion using common LCN production methods.…”
Section: ■ Introductionmentioning
confidence: 99%